2010
DOI: 10.3928/01484834-20091217-03
|View full text |Cite
|
Sign up to set email alerts
|

Role-Playing in Nursing Theory: Engaging Online Students

Abstract: The teaching and learning of nursing theory, at all program levels, is challenging due to the complexity and abstract nature of its content, the dry nature in which the study of theory often is approached, a perception of disconnect from practice, and faculty discomfort and avoidance of the subject matter. Adapting creative educational strategies to the online environment is an ongoing challenge for educators. Role-play relates well to the constructivist basis of creating personal meaning based on the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
0
15
0
7
Order By: Relevance
“…In another study conducted on nurses, educational activities involving role play with peers resulted in a learning experience that was more interactive, and which provided the students with an active learning environment. These activities also encouraged the students to learn, and was very favourably received with regard to both content and method [5]. The learning environment provided by role playing is very important in allowing the students to feel like doctors.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted on nurses, educational activities involving role play with peers resulted in a learning experience that was more interactive, and which provided the students with an active learning environment. These activities also encouraged the students to learn, and was very favourably received with regard to both content and method [5]. The learning environment provided by role playing is very important in allowing the students to feel like doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Role-play provides students with an opportunity to be actively involved in the construction of their own learning therefore allowing for multi-level brain processing of experiences (Clapper, 2010;Levitt & Adelman, 2010;Nehring & Lashley, 2009). Role-play engages the motor as well as the cognitive system which, according to research allows the entire brain to be engaged in learning (Clapper, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The other 17 articles presented significant differences in the nature and structure of courses where drama education was used. Examples of courses containing drama were: an online core professional issues course (Levitt and Adelman, 2010), a nurse training program involving the study of ethical and legal issues in a nursing module (McAlinden, 2010), an undergraduate course on teen sexuality (SmithBattle, 2012), a second semester medical-surgical course (Tuxbury et al, 2012) and as part of the course work in the synthesis (clinical capstone) course (Welsh and Lowry, 2011).…”
Section: Level and Coursementioning
confidence: 99%
“…In a number of the articles drama was used to develop teaching and learning in order to make theoretical knowledge more accessible in practical situations, so that the students could apply their theoretical knowledge in practice (Austin et al, 2013;Ekebergh et al, 2004;Ekebergh, 2005;Levitt and Adelman, 2010). In many of the articles it was found that the actual classroom experience could be enhanced by the use of drama, and students could become more involved in their own learning since they themselves become the experts as they explored different situations together (Buxton, 2011;McClimens and Scott, 2007;McGarry and Aubeeluc, 2013).…”
Section: Support Students Learningmentioning
confidence: 99%